Rosemary Grasshopper Schistocerca ceratiola Hubell and Walker - John L. Capinera (EDIS)
The rosemary grasshopper occurs only in Florida. It is poorly known and rarely seen except by those specifically seeking it out. This 4-page fact sheet includes an illustrated summary of its appearance and ecology, written by John L. Capinera and published by the UF Department of Entomology and Nematology, July 2011.